Un modèle mensuel du secteur financier au Canada - Masson, Paul; Clinton, Kevin (L'Actualité économique, 1976)
AbstractIn this article we describe preliminary estimates of a model of the Canadian financial system. At the present time, the model explains the behaviour of the authorities, the chartered banks, the public, and the trust and mortgage loan companies. The variables explained include monetary aggregates, several interest rates, and the major assets of the chartered banks and of the trust and mortgage loan companies.The model differs from existing Canadian models in that we use monthly data rather than quarterly or annual data. We think the shorter observation period permits the econometric estimates to capture the dynamic adjustment processes more accurately. In particular, the mean lags implied by our equations tend to be considerably shorter than those in existing models. Another difference with conventional models is the larger influence given to asset and liability management of the chartered banks in the determination of short-term interest rates.The model is intended primarily for forecasting, and results are presented which indicate its usefulness in that regard.